Cheirotonia and Ordination - Every, George (Scottish journal of theology, 1956)
The verb ordinare and its cognates have been used for the setting apart of church officers ever since Latin began to be an ecclesiastical language. It is significant that the names of the offices were transliterated; cheirotonia, the laying-on-of-hands, was not. This no doubt may be very simply explained. Actions with the hands were used in healing, in the reconciliation of penitents, in the ceremonies in and after baptism. A distinction of terms was needed; the choice of a term points forward to the whole history of Latin Christendom.